Time and distance: Reflections on local and global history from East Africa - Reid, R (Cambridge University Press, 2019)
This paper is concerned with East Africans’ perceptions of the intersection between their own, highly charged and contested, local histories, and the global past, as well as their place in it. The two case studies on which the paper is based – Eritrea and Uganda – have much in common in terms of recent history, not least in their experience of prolonged violence, and thus taken together they elucidate distinctive characteristics. Yet they also illustrate broader phenomena. On one level, particular interpretations of local history – both the deeper, precolonial past, and the more recent, twentieth-century past – are utilised to critique the flow of global history, as well as the impositions of globalization, and to emphasize the bitter experience of marginality and lack of agency. At the same time, the global past – conceptualized as the evolution of an intrusive, imperialist, hypocritical global order imposed by foreigners, usually Western in provenance – is seen as omnipresent and pervasive, and thus the arguments made around marginality serve to remind us, paradoxically, how central these communities are (or should be) to the framing of global history.